2018
DOI: 10.1021/acs.jafc.8b01413
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine Triggers Mitochondrial Dysfunction and Oxidative Stress in Quail (Coturnix C. coturnix) Cerebrum via Activating Xenobiotic-Sensing Nuclear Receptors and Modulating Cytochrome P450 Systems

Abstract: The residues from the widely used broad-spectrum environmental herbicide, atrazine (ATR), result in the exposure of nontarget organisms and persist as a global major public health hazard. ATR is neurotoxic and may cause adverse health effects in mammals, birds, and fishes. Nevertheless, the molecular mechanism of ATR induced neurotoxicity remains unclear. To assess the molecular mechanisms of ATR-induced cerebral toxicity through potential oxidative damage, quail were treated with ATR by oral gavage administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(16 citation statements)
references
References 85 publications
3
13
0
Order By: Relevance
“…Similar findings have been reported in a study carried out in quail that evaluated the actions of atrazine, a NR1I2 ligand (Abass et al, 2012) and widely employed neurotoxic herbicide (Lin et al, 2018). Chronic exposure to increasing doses of atrazine resulted in mitochondrial dysfunction, elevated ROS production, induction of apoptosis in the cerebrum and cerebellar toxicity (Lin et al, 2018;Xia et al, 2017). Furthermore, atrazine increased the cerebral and cerebellar expression of NR1I2, NR1I3 and AhR, suggesting that activation of these NRs is responsible for the upregulation of expression of CYP450 isoforms (Lin et al, 2018;Xia et al, 2017).…”
Section: Nr1i3 (Car) and Nr1i2 (Pxr): Roles In Neurotoxicitysupporting
confidence: 88%
See 3 more Smart Citations
“…Similar findings have been reported in a study carried out in quail that evaluated the actions of atrazine, a NR1I2 ligand (Abass et al, 2012) and widely employed neurotoxic herbicide (Lin et al, 2018). Chronic exposure to increasing doses of atrazine resulted in mitochondrial dysfunction, elevated ROS production, induction of apoptosis in the cerebrum and cerebellar toxicity (Lin et al, 2018;Xia et al, 2017). Furthermore, atrazine increased the cerebral and cerebellar expression of NR1I2, NR1I3 and AhR, suggesting that activation of these NRs is responsible for the upregulation of expression of CYP450 isoforms (Lin et al, 2018;Xia et al, 2017).…”
Section: Nr1i3 (Car) and Nr1i2 (Pxr): Roles In Neurotoxicitysupporting
confidence: 88%
“…Similar findings have been reported in a study carried out in quail that evaluated the actions of atrazine, a NR1I2 ligand (Abass et al, 2012) and widely employed neurotoxic herbicide (Lin et al, 2018). Chronic exposure to increasing doses of atrazine resulted in mitochondrial dysfunction, elevated ROS production, induction of apoptosis in the cerebrum and cerebellar toxicity (Lin et al, 2018;Xia et al, 2017).…”
Section: Nr1i3 (Car) and Nr1i2 (Pxr): Roles In Neurotoxicitysupporting
confidence: 85%
See 2 more Smart Citations
“…In agreement, the present study showed that 8:2 FTOH decreased the activities of SOD and CAT in both the liver and serum and reduced GSH content in serum (Figure ), indicating that 8:2 FTOH exposure caused oxidative stress in vivo. Oxidative stress damages biological molecules and thus mediates cellular and tissue injury caused by many xenobiotics . N 鈥恆cetylcysteine, an antioxidant, reduced PFOA鈥恑nduced apoptosis in human hepatoma cells .…”
Section: Discussionmentioning
confidence: 99%